A novel constrained optimal tuning method with application to helicopter rotor track and balance. (1st February 2023) - Wang, Chuanda; Huang, Guoke; Li, Fei; Yu, Guorui; Yi, Hui; Peng, Haijun
Highlights: A novel constrained optimal tuning method for rotor track and balance are proposed. The optimality and stability of proposed control method are mathematically proof. Real-time software and experimental hardware layouts are designed and built. Wind tunnel experiments show the non-uniformity between blades is improved. Abstract: Low-frequency vibration and blade track spread caused by non-uniform mass and aerodynamic distributions in the main rotor system may affect pilot's health and shorten the life span of helicopter components. To eliminate these hazards, the manual passive maintenance procedure on the ground is adopted, but it is typically complex, time-consuming, and expensive; and the other existing active control algorithms do not simultaneously minimize the once- per -revolution (1/rev) vibration and blade track spread with complicated parameter tuning. In this work, a constrained optimal tuning (COT) method, is proposed to suppress both rotor 1/rev vibration and blade track spread utilizing pitch rod lengths as the control inputs. The COT method defines a constrained vibration control formulation, and it takes the track and the stroke range of pitch rods as a control constraint to ensure that the track spread is within specification and that the control inputs have no effect on the rotor's performance. Moreover, the optimality and stability of the COT are mathematically proven. The numerical simulations about non-uniform rotor were performed successfully utilizing the established main rotor dynamic model. The results show that the 1/rev vibration in the X, Y, and Z directions can all be decreased by more than 90 %, and the track spread can be reduced by more than 80 %. The introduction of input constraints maintains the control safety while also easing the burden of parameter tuning. Meanwhile, the 2/rev components of the lateral forces are similarly reduced. Furthermore, the control algorithm is modeled in software and built into real-time code to verify its effectiveness through the wind tunnel experiments. The experimental results reveal that 1/rev vibration is effectively reduced in three directions. The proposed controller also improves the aerodynamic environment of the blades, reducing almost all strange harmonic components (n-0.5)/rev (n = 1 to 10) to near zero.